2021
DOI: 10.3389/fmolb.2021.644644
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of Class B GPCR Selectivity for the Neuropeptides PACAP and VIP

Abstract: The related neuropeptides PACAP and VIP, and their shared PAC1, VPAC1 and VPAC2 receptors, regulate a large array of physiological activities in the central and peripheral nervous systems. However, the lack of comparative and molecular mechanistic investigations hinder further understanding of their preferred binding selectivity and function. PACAP and VIP have comparable affinity at the VPAC1 and VPAC2 receptor, but PACAP is 400–1,000 fold more potent than VIP at the PAC1 receptor. A molecular understanding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…The multifarious physiological effects of PACAP are mediated through binding to different G protein-coupled receptors, including PAC1 (PAC1-R), VPAC1 (VPAC1-R) and VPAC2 (VPAC2-R) receptors [35] (Figure 1). PAC1-R exerted a 100-fold higher affinity for PACAP than for VIP, whereas VPAC1-R and VPAC2-R exhibit a comparable affinity to PACAP and VIP [36]. Molecular studies identified diverse receptor conformational ensembles and microstate transition paths for each receptor and revealed differential peptide-receptor interactions (at the atomistic detail) for each receptor important for PAC1, VPAC1 and VPAC2 receptor ligand selectivity [37].…”
Section: Pacap Receptors and Their Localization In The Gi Tractmentioning
confidence: 99%
See 1 more Smart Citation
“…The multifarious physiological effects of PACAP are mediated through binding to different G protein-coupled receptors, including PAC1 (PAC1-R), VPAC1 (VPAC1-R) and VPAC2 (VPAC2-R) receptors [35] (Figure 1). PAC1-R exerted a 100-fold higher affinity for PACAP than for VIP, whereas VPAC1-R and VPAC2-R exhibit a comparable affinity to PACAP and VIP [36]. Molecular studies identified diverse receptor conformational ensembles and microstate transition paths for each receptor and revealed differential peptide-receptor interactions (at the atomistic detail) for each receptor important for PAC1, VPAC1 and VPAC2 receptor ligand selectivity [37].…”
Section: Pacap Receptors and Their Localization In The Gi Tractmentioning
confidence: 99%
“…The PAC1-R has various variant transcripts (Null, Hip, Hop1, Hop2, Hiphop1, Hiphop2, short and very short isoforms), which lead to the activation of two different signaling pathways: increasing the intracellular level of cyclic AMP (cAMP) by adenylyl cyclase (AC) and the stimulation of phospholipase C (PLC) [36,38]. Activation of VPAC1-R and VPAC2-R stimulate AC and some other cAMP-independent signaling cascades [39].…”
Section: Pacap Receptors and Their Localization In The Gi Tractmentioning
confidence: 99%
“…Most of the neural and peripheral tissues known to date contain the PAC1null or PAC1hop isoforms that includes a 21-amino acid insert in the ECD (Figure 1), which is missing in available PAC1R structures in the PDB (May and Parsons, 2017). This ECD insert was found highly dynamic in our previous modeling studies (Liao et al, 2017;Liao et al, 2021), but its role in regulating PAC1R remains unknown. While PAC1R antagonists are being developed as potential treatments for stress-related disorders, the agonist-bound cryo-EM structures are not directly applicable to computational design or screening of PAC1R antagonists.…”
Section: Introductionmentioning
confidence: 98%
“…Class B GPCRs (the secretin peptide receptors) play a crucial role in maintaining hormonal homeostasis in the human body. The structure of class B GPCRs consists of an extracellular domain (ECD) and a seven-transmembrane domain (TMD) [22] , [23] , [24] , [25] , [26] , [27] . The human glucagon receptor (GCGR) is a prototypical class B GPCR.…”
Section: Introductionmentioning
confidence: 99%